Enhancing children's well‐being using Malaysian‐adapted version Super Skills for life (M‐SSL) among primary school children in Malaysia - Chen, Yoke Yong; Ting, Chuong Hock; Siti Raudzah, Ghazali; Ang, Ai Ling (Wiley Periodicals LLC., 2024)
With the increasing prevalence of mental health issues among children, there is a growing need to implement school‐based preventive programs for emotional well‐being in Malaysia. Super Skills for Life (SSL) is a transdiagnostic preventive program designed based on the cognitive‐behavioral therapy concept to address emotional problems among children. This study examined the effectiveness of the M‐SSL program in reducing depressive and anxiety symptoms as well as other psychological issues such as social competency, worries, cognitive and emotional regulation in a sample of Malaysian children between the ages of 10 and 12. A quasi‐experimental preiand postintervention research design was conducted. A total of 165 primary school children (M = 10.9, SD = 0.72) were recruited with 88 of them randomly assigned to the intervention group. All of them were asked to complete a questionnaire consisting of demographic data, the Centre for Epidemiologic Studies Depression Scale Revised, Spencer Children's Anxiety Scale, Strength and Difficulties Questionnaires, Social Skills Questionnaires and Cognitive Emotional Regulation Questionnaires. Children in the M‐SSL group significantly reported lower levels of depres-sive scores during follow‐up assessment compared to the children in the control group. They also showed significantimprovement in their depressive subscale scores, socialworries scores, and the way they perceived an event ascompared to the control group. These findings provideinitial support for the effects of M‐SSL, suggesting that it isa valuable resource for the prevention of depressivesymptoms and for improving social worries among children.